Far red/near infrared light-induced protection against cardiac ischemia and reperfusion injury remains intact under diabetic conditions and is independent of nitric oxide synthase - Keszler, Agnes; Brandal, Garth; Baumgardt, Shelley; Ge, Zhi-Dong; Pratt, Phillip F.; Riess, Matthias L.; Bienengraeber, Martin (Frontiers in Physiology, 2014)
Far red/near-infrared light (NIR) promotes a wide range of biological effects including tissue protection but whether and how NIR is capable of acutely protecting myocardium against ischemia and reperfusion injury in vivo is not fully elucidated. Our previous work indicates that NIR exposure immediately before and during early reperfusion protects the myocardium against infarction through mechanisms that are nitric oxide (NO)-dependent. Here we tested the hypothesis that NIR elicits protection in a diabetic mouse model where other cardioprotective interventions such as pre- and postconditioning fail, and that the protection is independent of nitric oxide synthase (NOS). NIR reduced infarct size dose dependently. Importantly, NIR-induced protection was preserved in a diabetic mouse model (db/db) and during acute hyperglycemia, as well as in endothelial NOS−/− mice and in wild type mice treated with NOS inhibitor L-NAME. In in vitro experiments NIR light liberates NO from nitrosyl hemoglobin (HbNO) and nitrosyl myoglobin (MbNO) in a wavelength-(660-830 nm) and dose-dependent manner. Irradiation at 660 nm yields the highest release of NO, while at longer wavelengths a dramatic decrease of NO release can be observed. Similar wavelength dependence was observed for the protection of mice against cardiac ischemia and reperfusion injury in vivo. NIR-induced NO release from deoxymyoglobin in the presence of nitrite mildly inhibits respiration of isolated mitochondria after hypoxia. In summary, NIR applied during reperfusion protects the myocardium against infarction in an NO-dependent, but NOS-independent mechanisms, whereby mitochondria may be a target of NO released by NIR, leading to reduced reactive oxygen species generation during reperfusion. This unique mechanism preserves protection even during diabetes where other protective strategies fail.